2019
DOI: 10.1038/s41533-019-0137-7
|View full text |Cite
|
Sign up to set email alerts
|

Real-life prescribing of asthmatic treatments in UK general practice over time using 2014 BTS/SIGN steps

Abstract: The 2014 British Thoracic Society (BTS) and Scottish Intercollegiate Guideline Network (SIGN) guidelines recommend a stepwise approach to asthma management. We investigated the management of asthma in primary care in the UK to understand how real-world practice compares with BTS/SIGN guidelines. Asthma patients were identified from the UK Clinical Practice Research Datalink from September 2006 to August 2016. Aims were to classify patients according to BTS/SIGN steps, describe the proportion of patients transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Our study focused on those who were being 'stepped up' to asthma maintenance therapy, as these patients represent a group who have objectively experienced an acute or sub-acute worsening of symptoms. This contrast with the approach taken by Gayle et al (22) who considered all asthmatics, regardless of severity, and the vast majority of individuals were at BTS/SIGN step 0 or step 1 which may have masked the treatment needs and trajectories of those with more severe asthma.…”
Section: Discussionmentioning
confidence: 86%
“…Our study focused on those who were being 'stepped up' to asthma maintenance therapy, as these patients represent a group who have objectively experienced an acute or sub-acute worsening of symptoms. This contrast with the approach taken by Gayle et al (22) who considered all asthmatics, regardless of severity, and the vast majority of individuals were at BTS/SIGN step 0 or step 1 which may have masked the treatment needs and trajectories of those with more severe asthma.…”
Section: Discussionmentioning
confidence: 86%
“…Asthma treatment classifications such as the BTS/SIGN steps and the GINA steps have been used previously for both population-level [8,22] and individual-level analyses [32,39,40]. Previous studies using the BTS/SIGN steps have interpreted and implemented the guidelines in different ways [8,22,28,29], and indeed the guidelines have also been updated over time, making direct comparisons challenging. There are four main strengths of the methods described herein for the identification of asthma treatment regimens, and their mapping to BTS/ SIGN treatment steps.…”
Section: Results In Contextmentioning
confidence: 99%
“…Previous studies using the BTS/SIGN steps [8,22,28,29] have often faced some combination of three key weaknesses. First, not all possible or observed regimens map to an explicit treatment step, and thus require adhoc judgements to be made.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of our study largely corroborate those found in a study in the UK. 21 Gayle et al studied real-life prescribing of asthma treatment in general practices over time. They found that most adults stayed within the same treatment step over a 6-month interval.…”
Section: Discussionmentioning
confidence: 99%